PENDAMPINGAN PENYUSUNAN LAPORAN KEUANGAN DAN PENERAPAN DIGITAL MARKETING PADA UMKM ANGKRINGAN SOR TALOK - Naila Dewi, Zhafira; Wafa, Zaenal (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
The rapid growth of micro, small, and medium enterprises (MSMEs) has been accompanied by intense competition. Without proper financial planning and the application of digital marketing, MSMEs will find it difficult to grow and may be outperformed by competitors. Entrepreneurs, especially those at Angkringan Sor Talok, are prone to making mistakes in recording financial reports due to a lack of knowledge and skills needed to document them accurately and completely. Moreover, these MSMEs have not yet implemented digital marketing, which is essential in today’s era. Therefore, this community service program aims to provide a basic understanding of financial reporting, particularly in recording financial transactions, and to facilitate bookkeeping as well as the use of digital marketing through the Google Maps platform. The methods used include surveys, socialization, and training. This program benefits business owners, especially at Angkringan Sor Talok, by helping them improve financial recording, expand market reach, and increase sales in the digital era.